2019
DOI: 10.1002/bjs5.50234
|View full text |Cite
|
Sign up to set email alerts
|

Transanal total mesorectal excision for locally advanced middle–low rectal cancers

Abstract: Background This study investigated the results of transanal total mesorectal excision (TaTME) combined with laparoscopy for locally advanced mid–low rectal cancer. Methods Patients with mid–low locally advanced rectal cancer (T3 category or above and/or N+) who underwent rectal resection with TaTME technique were enrolled prospectively. Patients who had distant metastasis, multiple malignancies, intestinal obstruction or perforation, or a clinical complete response to chemoradiotherapy were excluded. Postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…8,10 Both advantages and disadvantages associated with the procedure of taTME, which concern the technical feasibility of taTME. A retrospective study by Thien et al 13 reported a mean duration of surgery of 210 min with single team. In later stages of enrollment, six patients underwent surgery with double teams, and mean duration was 150 min (p = .002).…”
Section: Feasibilitymentioning
confidence: 99%
See 4 more Smart Citations
“…8,10 Both advantages and disadvantages associated with the procedure of taTME, which concern the technical feasibility of taTME. A retrospective study by Thien et al 13 reported a mean duration of surgery of 210 min with single team. In later stages of enrollment, six patients underwent surgery with double teams, and mean duration was 150 min (p = .002).…”
Section: Feasibilitymentioning
confidence: 99%
“…In later stages of enrollment, six patients underwent surgery with double teams, and mean duration was 150 min (p = .002). 13 In this context, Chen et al 14 reported that the duration of surgery can be markedly reduced by using a two-team approach. Meanwhile, Mege et al 15 evaluated 34 consecutive patients who underwent taTME and did not observe a significant difference in operating time between standard laTME and taTME with a single surgical team (237 ± 48 vs. 260 ± 45 min, p = .1).…”
Section: Feasibilitymentioning
confidence: 99%
See 3 more Smart Citations